Flame Photometric Method for the Estimation of Iodine in Common Salt of Different Brands - Kumar A; B. Anroop; Gupta A.K; Singh B.K (International Journal of Pharma and Bio Sciences, 2010)
A simple, rapid, sensitive and precise flame photometric method has been developed for the quantitative estimation of Iodine in common salt. Working range of concentration was found to be between 3.246 to 110.357mcg/ml. Regression equation was found to be y = 0.8036 x + 0.3273 and coefficient of correlation was 0.9994. The recovery studies confirmed the accuracy of the proposed method.